Resistance to Azole Drugs by Fungal Species Isolated from Date Palm Samples within Lafia Metropolis, Nigeria (Lafia Journal of Scientific and Industrial Research, 2024)
Fungal species infecting fruits are developing resistance to some antifungals. The study determined prevalent fungi in date palm fruits and their resistance to azole antifungals. Dried date palm fruit samples were collected from Modern Market, Old Market, Alhamis Market, Koro Market and Tomato Market in Lafia Metropolis, Nigeria and fungi isolated from them. Antifungal susceptibility test as a zone of inhibition of fungal mycelial growth were recorded for terbinafine, clotrimazole, nystatin, metronidazole and fluconazole. Dates from the old market had the highest contamination with 6.0×103 ± 4.2 cfu/g, while samples from Koro market with 2.5×103 ± 1.7 cfu/g were the least contaminated. A total of 84 fungi were isolated, Aspergillus niger was the most predominant species while Aspergillus versicolor was the least predominant. Terbinafine was the most effective azole against the fungal species isolated with a zone of inhibition of 43 mm in diameter, while fluconazole was the least effective with the zone of inhibition of 0 mm. The organism most susceptible to the antifungal drugs was Aspergillus niger, while Penicillium chrysogenum was the most resistant. Results of this study indicated that, date palm fruits around the Lafia markets were more susceptible to Aspergillus niger contamination than other fungal species, and Terbinafine was the best azole antifungal drug. The study recommends that further research should be carried out with respect to the resistance developed against azoles by the fungal species.